The role of platelet desialylation as a biomarker in primary immune thrombocytopenia: mechanisms and therapeutic perspectives - Zhang, Qianhui; Huang, Miao; Thomas, Elizabeth Rosalind; Wang, Lu; Liu, Jia; Li, Xiang; Luo, Jiesi; Zou, Wenjun; Wu, Jianming (Frontiers in Immunology, 2024)
Primary immune thrombocytopenia (ITP) is an acquired autoimmune disorder characterized by the destruction of platelets. Although it was long believed that the critical role of autoantibodies in platelet destruction, primarily through the Fc-dependent platelet clearance pathway, recent findings indicate that the significance of the Fcindependent platelet clearance pathway mediated by hepatocytes, thus shedding light on a previously obscure aspect of ITP pathogenesis. Within this context, the desialylation of platelets has emerged as a pivotal biochemical marker. Consequently, targeting platelet desialylation emerges as a novel therapeutic strategy in the pathogenesis of ITP. Notably, prevailing research has largely focused on antiplatelet antibodies and the glycosylationassociated mechanisms of platelet clearance, while comprehensive analysis of platelet desialylation remains scant. In response, we retrospectively discuss the historical progression, inducing factors, generation process, and molecular regulatory mechanisms underlying platelet desialylation in ITP pathogenesis. By systematically evaluating the most recent research findings, we contribute to a comprehensive understanding of the intricate processes involved. Moreover, our manuscript delves into the potential application of desialylation regulatory strategies in ITP therapy, heralding novel therapeutic avenues. In conclusion, this manuscript not only fills a critical void in existing literature but also paves the way for future research by establishing a systematic theoretical framework. By inspiring new research ideas and offering insights into the development of new therapeutic strategies and targeted drugs, our study is poised to significantly advance the clinical management of ITP.